KEBEBASAN DAN KESETARAAN SEBAGAI DUA NILAI SOSIAL DASAR MASYARAKAT MODERN (Sebuah Studi Aksiologi tentang Demokrasi) - Binsasi, Norbertus Antoine (Universitas Jabal Ghafur, 2024)
Today, democracy is considered a political system that is believed by many people in the world to be the best for achieving national goals. In its development, democracy is no longer limited to a form of government but has become a value that exists in modern society. Democracy contains two main values, namely the values of freedom and equality. The purpose of this study is to find the essence of the birth of the concept of democracy, its characteristics and functions using the semiotic interpretation method. This study produces the answer that democracy was born from human responses to the fact of living together that if humans in living together are not regulated, they will not achieve their individual activities, and living together is regulated within the framework of democracy. This study also found the answer that democracy has historical, spiritual, dynamic, and normative characteristics, in addition democracy has a hermeneutical function and an ethical function.Keywords: value of freedom, value of equality, contextual democracy, local democracy, doctrinal democracy